A dosimetry study precisely outlining the heart substructure of left breast cancer patients using intensity‐modulated radiation therapy. (8th September 2014) - Fan, Ling‐li; Luo, Yang‐kun; Xu, Jing‐hui; He, Ling; Wang, Jie; Du, Xiao‐bo
Abstract : The purpose of this study was to evaluate the feasibility of delineating the substructure of the heart by using 64‐slice spiral CT coronary angiography (CTA) in breast cancer patients who underwent left breast‐conserving surgery, and to compare the dosimetric differences between the targets and organs at risk in the prone and supine positions in intensity‐modulated radiation therapy (IMRT) planning. From January to December 2011, ten patients who underwent left breast‐conserving surgery were enrolled in this study. CTA was performed in both the supine and prone positions during the simulation, and conventional scanning without CTA was performed at the same time. Image registration was performed for paired image series using a commercially available planning system. In a conventional image series, the clinical target volume (CTV) of the whole breast, planning target volume (PTV), bilateral lungs (L‐Lung, R‐Lung), spinal cord, contralateral breast (R‐Breast), and heart were delineated. In the CTA image series, the left ventricular (LV) and left anterior descending coronary arteries (LAD) and the planning risk volume (LAD‐PRV) of the LAD (LAD with a 1 cm margin) were outlined. For each patient, two separate IMRT plans were developed for the supine and prone positions. A total of 20 plans were generated. The following indicators were compared: Dmean and D95 for the PTV; Dmean, V5, and V20 for the left lung; Dmean, V10, V20, V25, V30, and V40 for the heart and its substructures (LAD‐PRV, LV); Dmean and V5 for the right lung; and Dmax and Dmean for the right breast. Using CTA to delineate the substructures of the heart is simple and straightforward. Plans for both the prone and supine positions reached the prescribed dose for the PTV without significant differences. Dose distributions were acceptable for both the prone and supine positions. However, the LAD‐PRV, LV, heart, and L‐Lung received smaller doses in the prone position plans than in the supine position plans. The Dmean values reduced by 445.83 cGy ( p = 0.043 ), 575.00 cGy ( p = 0.003 ), 402.00 cGy ( p = 0.039 ), and 553.33 cGy ( p = 0.004 ) in the LAD‐PRV, LV, heart, and L‐Lung. In addition, the V25 lessened 12.54 % ( p = 0.042 ) and 8.70 % ( p = 0.019 ) in the LV and heart, while the V20 was decreased 8.57 % ( p = 0.042 ), 15.21 % ( p = 0.026 ), 12.59 % ( p = 0.011 ), and 10.62 % ( p = 0.006 ) in the LAD‐PRV, LV, heart, and L‐Lung, respectively. Similarly, the V10 and V30 were reduced by 28.31% ( p = 0.029 ) and 5.54 % ( p = 0.034 ) in the heart, while the V5 was cut back 27.86 % ( p = 0.031 ) in the L‐Lung. For most Asian women with average‐sized breasts after breast conserving treatment (BCT), prone positioning during IMRT radiation will reduce the dose to the ipsilateral lung, heart, and substructures of the heart, which may reduce the incidence of cardiovascular events after radiotherapy more than radiation therapy performed in a supine position. Using CTA to delineate the substructures of the heart is easy and intuitive. It is cost‐effective and highly recommended for breast cancer IMRT. However, the dose‐volume limits of the heart substructures remain to be determined. PACS number: 87.55.dk